Effect of Fertilizer Levels and Foilar Application on Morphological Characters, Nutrient Content and Yield of Cotton - Deshpande, A. N.; Masram, R. S.; Kamble, B. M. (International Journal of Bio-resource and Stress Management, 2015)
A field experiment on effect of fertilizer levels and foliar application on morpho-physiological, nutrient content, reddening and yield of cotton on Vertisol” was conducted at Cotton Improvement Project, Mahatma Phule Krishi Vidyapeeth, Rahuri, Maharashtra, India during May to September, 2008-09. The experiment was laid out in a factorial randomized block design with three replications and two main treatments i.e. hybrid Bt RCH-2 and Non-Bt RCH-2 and nine sub treatments with different fertilizer doses i.e. 50% recommended dose of fertilizer (RDF), 75% RDF, 100% RDF, 125% RDF, 150% RDF, 100% RDF+2% DAP spray, 100% RDF+1% MgSO4 and 100% RDF+1% KNO3. The non-Bt cotton hybrid showed pronounced effect on growth parameters than Bt cotton hybrid. The treatment 100% RDF at square and flowering recorded significant effects on biochemical parameters (Chlorophyll N, P, K, Mg and Fe content), which was maximum in non-Bt hybrid as compared to Bt cotton hybrid. At boll development stage, treatment 100% RDF+1% MgSO4 was found to be the best for highest chlorophyll content in non-Bt than Bt cotton. The nutrient concentration in leaf was higher at square formation and goes on reducing as plant growth proceeded. The application 100% RDF along with three foliar sprays of 1% KNO3 or 1% MgSO4 or 2% DAP was found minimum intensity of reddening of leaves and increased yield of cotton.